2008
DOI: 10.1111/j.1728-4457.2008.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Biological Risk Factors in Two Populations: The United States and Japan

Abstract: Life expectancy is higher in Japan than in the United States. We compared the prevalence of clinically recognized risk factors in the two countries to explore the possibility that differences in these likely precursors to disease and death are linked to the paths to higher mortality for Americans. We found that American men and women have higher levels of total biological risk than the Japanese, particularly for risk factors included in the metabolic syndrome. A significant difference between the two countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Researchers have long been interested in Japanese longevity, but the mechanisms of the phenomenal health of the Japanese people remain to be firmly established. While past research has tended to focus on biological and functional factors, such as biomarkers (Crimmins, Vasunilashorn, Kim, Hagedorn, & Saito, 2008), blood pressure (Davarian, Crimmins, Takahashi, & Saito, 2013), and obesity (Reynolds et al, 2008), this study brings new evidence to bear on this topic: Social factors might be just as important as individual characteristics in the production and distribution of health. Overall, in the face of the rapidly aging population, more research and policy attention should be directed toward the social and cultural circumstances in which older individuals are embedded.…”
Section: Resultsmentioning
confidence: 95%
“…Researchers have long been interested in Japanese longevity, but the mechanisms of the phenomenal health of the Japanese people remain to be firmly established. While past research has tended to focus on biological and functional factors, such as biomarkers (Crimmins, Vasunilashorn, Kim, Hagedorn, & Saito, 2008), blood pressure (Davarian, Crimmins, Takahashi, & Saito, 2013), and obesity (Reynolds et al, 2008), this study brings new evidence to bear on this topic: Social factors might be just as important as individual characteristics in the production and distribution of health. Overall, in the face of the rapidly aging population, more research and policy attention should be directed toward the social and cultural circumstances in which older individuals are embedded.…”
Section: Resultsmentioning
confidence: 95%
“…Links between blood‐C levels and age, sex, and hemoglobin (Hb) levels are also investigated (Au and Schilling, 1986; Crimmins et al, 2008a, b; Inouye et al, 1999; Mjos et al, 1977; Oguntibeju, 2003; Wilson et al, 1994). Because childhood infections can stunt growth by reallocating resources for development to combat infection, we include stunted height as an indicator of past exposure to infection (Crimmins and Finch, 2006a, b; Finch, 2007; Finch and Crimmins, 2004; Godoy et al, 2009; McDade et al, 2007, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…For each indicator we use clinical cutpoints or widely used research-based cutpoints to indicate high levels of risk which are shown in Table 1 [39, 43, 45]. …”
Section: Methodsmentioning
confidence: 99%